Effects of inducer tip clearance on the performance and flow characteristics of a pump in a turbopump. (August 2017) - Kim, Changhyun; Kim, Semi; Choi, Chang-Ho; Baek, Jehyun
A turbopump is used to pressurize propellants to gain high thrust in a projectile and consists of two pumps and a turbine. The pumps usually employ an inducer upstream to prevent performance deterioration by lowering net positive suction head required of the main impeller. However, several types of cavitation and instabilities take place in the flow field. Therefore, numerous experiments and CFD analysis for turbopumps have been conducted. Especially, there were some previous studies on inducer tip clearance, but they were limited to inducer regions due to the complexity of simulating the entire pump. In this study, the flow through an oxidizer pump in a turbopump was numerically investigated with four different sizes of inducer tip clearances. ANSYS CFX 13.0 with Rayleigh–Plesset equation was used to test flows in both non-cavitating and cavitating conditions. In the non-cavitating condition, the pump with the largest inducer tip clearance showed the worst head rise, efficiency and huge size of backflow arose near inducer casing. Also, the vortex was generated between the inducer blades in the case of large inducer tip clearance due to weak tip leakage flow. In the cavitating condition, the inducer with large tip clearance was found to be vulnerable to low suction pressure and floating cavity was observed between the inducer blades. However, the heads of the pumps with different inducer tip clearances were broken down at similar cavitation numbers due to the blade cavitation near the impeller throat. In addition, the transferred cavity from the inducer region also induced head breakdown of the pump.